Study, fabrication and characterization of thin films for CZTS solar cells - Ali-Saoucha Salim (University of M'Sila, 2024)
This study primarily investigates CZTS thin-film solar cells. We employ numerical modeling through Silvaco Atlas and AMPS-1D software to analyze CZTS solar cells, including substrate, bifacial, and tandem configurations. A notable aspect of our research involves proposing an innovative design for CZTS bifacial solar cells. We specifically examine the influence of the barrier height at the p-CZTS/n-TCO interface in the structure ZnO:Al/CdS/CZTS/TCO/SLG. The efficiency results reveal 15.8% under front-side illumination and 4% under back-side illumination. In the subsequent section, we utilize the Density Functional Theory (DFT) method to scrutinize the structure, electronic, and optic properties of the ZnS1-xOx alloy. Shifting our focus to experimentation, we employ the Sol-Gel spin-coating method to fabricate pure ZnO, sulfur-doped ZnO, and ZnS thin films. The spin-coated films are characterized by analyzing their structural, morphological, and optical properties through techniques such as X-ray diffraction (XRD), Atomic Force Microscopy (AFM), and UV-VIS spectroscopy.
ركزت هذه الاطروحة على دراسة الطبقات الرقيقة التي تدخل في صناعة الخلايا الشمسية المبنية على رقائق ( CZTS ( من الناحية النظرية باستعمال برنامجي ) Silvaco ( و ) AMPS-1D ( بمحاكات مختلف التركيبات الممكنة )أحادية الوجه، ثنائية الوجه، الترادفية( مع التركيز على ميزات رقائق الاوكسيد الناقل واستعمالاته كوجه شفاف او نافذة أو كطبقة وسيطة، كما تم باستعمال برنامج ) Wien2k ( حساب مختلف الخصائص الكهربائية و الضوئية لمركب ) x-1SxZnO ( ، ومن الناحية التطبيقية تم ترسيب رقائق من مركب ) ZnO ( و ) ZnO ( و) ZnO ) بنسب 2% ، 4% ، 8% باستعمال تقنية الطرد المركزي للمحلول الهلامي ،وتحديد خصائصها الهيكلية والمورفولوجية والبصرية باستعمال تحليل انحراف الاشعة السينية ) DRX ( و مجهر القوة الذرية )َ AFM ( و مطيافية الأشعة المرئية وفوق البنفسجية ( UV-vis .
Keywords: solar cells; thin films; ZnO; ZnS; ZnO:S; Silvaco; AMPS-1D.; الخلايا الشمسية، الطبقات الرقيقة، كبريت الزنك، أكسيد الزنك، التطعي م